Remedy for inverse scattering problems via space-mapping inverse-difference approach - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2015)
An inverse-scattering algorithm (ISA) based on integral-equation formulation is used as an inverse coarse model in the space-mapping inverse-difference (SMID) method and named as ISA-based SMID (ISA-SMID). The enhancement of ISA-SMID optimization over inverse-scattering algorithms is tested. To this aim, extraction of dielectric profile problem is examined with ISA-SMID, which is obtained by the hybridization of SMID and Newton-based inverse-scattering algorithm. The method of moments solution of integral equation is used in the utilized inverse algorithm for the reconstruction of complex permittivity of the inhomogeneous object loaded in the waveguide. © 2015 IEEE.